RURAL AREA DEVELOPMENT PROGRAM: VILLAGE DEVELOPMENT STRATEGY BASED ON RURAL-URBAN LINKAGES (A CASE STUDY: AGROWISATA IJEN RURAL AREA IN BANYUWANGI REGENCY) - Firda Diartika; Triyoso Astanto (Journal of Applied Economics in Developing Countries, 2020)
Rural development is an effort to optimally utilize all potential resources to achieve village growth and improve the welfare of rural communities. The direction of the village development policy was then reborn marked by the birth of a law that regulating villages (UU 6/2014). The rural area development program is one of the mandates of the law on villages and makes a difference between the previous village development. The purpose of this research is to identify the characteristics of rural area development program. This research was conducted with a deductive approach and qualitative research methods. Data collection was carried out through institutional surveys and field observations. Data analysis was performed using content analysis and triangulation strategy. The research results show that the rural area development program is included in the development strategy of rural-urban linkages with the characteristics of the target village of the program being a developing village with good accessibility to cities, the availability of adequate infrastructure, and there are production-distribution network and economic exchange from rural to cities. The characteristics of program delivery are a combination of top-down and bottom-up approaches with multi-stakeholder participation and cross-stakeholder institutions with local institutions as the main implementers. Keywords: Rural areas, Regional development, Program implementation